Pengaruh Brand Ambassador Dan Citra Merek Terhadap Keputusan Pembelian Azarine Cosmetic Di Pakuwon Mall Surabaya - Nabila Salsabila; Is Fadhillah (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This study aims to analyze Azarine Cosmetic in conducting brand ambassadors and brand image in influencing customer purchasing decisions as part of a marketing strategy. This research method uses a quantitative approach. Azarine cosmetic customer participants purchase azarine cosmetics through the sampling method at Pakuwon Mall Surabaya. The analytical tools used are validity, reliability, classical assumptions, and hypothesis testing. Data collection methods used through field research and literature. The results of this study indicate that the path analysis in the t-test for the first hypothesis (H1) shows with a significance level of 0.001 that Brand Ambassador affects Purchasing Decisions. Meanwhile, the results of the t-test path analysis for the second hypothesis (H2) show that brand image affects purchasing decisions at a significance level of 0.001. The regression coefficient shows a positive relationship, which indicates that (H2 accepted) purchasing decisions are influenced by brand image.